Implementation of Artificial Intelligence tools in the detection of fake and deepfake videos: Case of Radio Televisión Española (RTVE) - Sánchez Esparza, Marta; Palella Stracuzzi, Santa; Fernández Fernández, Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Concerns about the spread of false information have led media outlets to employ artificial intelligence (AI) to detect deepfakes. This research is descriptive-exploratory, a literature review and interviews were conducted. It reveals the transformative impact of AI by highlighting its use to verify the authenticity of content. In this area, RTVE combines traditional methodologies with others based on AI, and leads the development of several tools in collaboration with several universities. These tools have already yielded satisfactory results in the detection of these materials, strengthening the veracity of the information and increasing public confidence in their contents.